Construction and Application of Discrete-Time-Domain Framework -based Power-Grid State Space - Wei XIONG; Yue ZHANG; Jianzhong DOU; Baofeng JIANG; Lianfei SHAN (Zhongguo dianli, 2022)
To obtain the eigenvalue more efficiently and conveniently, a discrete time domain model (DTDM) based state space construction method is proposed for power grids, and the stability criterion of is presented. Compared with the traditional methods, the nonlinear components can be linearized naturally in the proposed method so as the construction of the power-grid state space is simple. Meanwhile, the DTDM based state space can capture a wider range of system information at one time and is not restricted by the model of electrical equipment. That is the whole state space of power grids can be obtained only by the DTDM of the components and the topology of the power grid. The calculation of the eigenvalue is simple and efficient, and it can give the trend of the eigenvalue and predict the stability of the power system.